Implementation of Recruitment, Training, and Work Environment Systems on Employee Performance at the BNN Office of Labuhanbatu Utara Regency - Bayu Febri Arrasyid; Elvina Elvina; Christine Herawati Limbong (Budapest International Research and Critics University, 2022)
This study was conducted to analyze the effect of the recruitment system, training, and work environment on employee performance at the BNN Office in North Labuhanbatu Regency. This study uses quantitative methods, with several analytical techniques such as classical assumption test, multiple linear regression test, hypothesis testing, and coefficient of determination. The results of the analysis of this study indicate that simultaneously and partially the independent variables have a positive and significant effect on the dependent variable, as evidenced by the recruitment variable (X1) has a valuetcount (3.28) > ttable (1.70) with a significant value less than the probability value of 0.05 or a significant value of 0.003 <0.05, thus it can be concluded that the recruitment variable (X1) has a positive and significant effect on employee performance. Training (X2) has a value of tcount (2.53) > ttable (1.70) with a significantly smaller value than the probability of 0.05 or 0.017 < 0.05, thus it can be concluded that training (X2) has a positive and significant effect on employee performance. The work environment (X3) has a value of tcount (4.63) > ttable (1.70) with a significantly smaller value than the probability of 0.05 or 0.000 <0.05, thus it can be concluded that the work environment (X3) has a positive and significant effect on employee performance. . The F test results show the Fcount value of 13.83 > Ftable 2.93 with a significance value of 0.000 <0.05. From these results, it can be concluded that recruitment (X1), training (X2), and work environment (X3) together have a positive and significant effect on employee performance (Y).